2014
DOI: 10.1590/0037-8682-0069-2014
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of potentially pathogenic Vibrio in oysters (Crassostrea gigas) and waters from bivalve mollusk cultivations in the South Bay of Santa Catarina

Abstract: Introduction:This research aimed to identify and quantify potentially pathogenic Vibrio from different cultivations of bivalve shellfi sh in the State of Santa Catarina, Brazil, and water regions in the South Bay, as well as correlate the incidence of these microorganisms with the physicochemical parameters of marine waters. Methods: Between October 2008 and March 2009, 60 oyster and seawater samples were collected from six regions of bivalve mollusk cultivation, and these samples were submitted for Vibrio cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
3
14
0
4
Order By: Relevance
“…Some studies have shown a linear relationship, similar to that of SST, when testing water samples (25,28,31,33). However, the data from our study did not show a particular correlation between salinity and V. parahaemolyticus in oyster samples, and these are results that are similar to those from some other studies (8,27,30,31,37). This could be related to the narrow range of salinity in our shellfish-growing areas.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have shown a linear relationship, similar to that of SST, when testing water samples (25,28,31,33). However, the data from our study did not show a particular correlation between salinity and V. parahaemolyticus in oyster samples, and these are results that are similar to those from some other studies (8,27,30,31,37). This could be related to the narrow range of salinity in our shellfish-growing areas.…”
Section: Discussionsupporting
confidence: 81%
“…Esse gênero também foi identificado por outros pesquisadores em diversos ambientes aquáticos no Brasil (Costa et al, 2008;Rebouças et al, 2011;Ramos et al, 2014). Na Baía do Sul, perto da Ilha de Santa Catarina, no Sul do Brasil, as espécies patogênicas de víbrio mais frequentes foram V. parahaemolyticus e V. vulnificus.…”
Section: Resultsunclassified
“…Na Baía do Sul, perto da Ilha de Santa Catarina, no Sul do Brasil, as espécies patogênicas de víbrio mais frequentes foram V. parahaemolyticus e V. vulnificus. Segundo os autores da pesquisa, houve uma correlação direta entre a temperatura elevada da água e o isolamento de V. vulnificus nesse ambiente (Ramos et al, 2014). Segundo Rebouças et al (2011), num trabalho realizado com água de cultivo de camarão no Ceará, o grande risco do isolamento de espécies de Vibrio está no fato desse gênero poder ser um reservatório para genes de patogenicidade, inclusive de resistência às drogas antimicrobianas, e nesse trabalho os autores perceberam que o padrão de resistência a essas drogas não estava relacionado a uma espécie apenas, mas ao gênero como um todo.…”
Section: Resultsunclassified
“…Esse gênero também foi identificado por outros pesquisadores em diversos ambientes aquáticos no Brasil Rebouças et al, 2011;Ramos et al, 2014). Na Baía do Sul, perto da Ilha de Santa Catarina, no Sul do Brasil, as espécies patogênicas de víbrio mais frequentes foram V. parahaemolyticus e V. vulnificus.…”
Section: Resultsunclassified